Editorial: Navigating modern Muslim consumerism: Behavioral insights, digital influence, and sharia financial innovation - Hendryadi, Hendryadi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2023)
This edition of Serambi Journal, Vol. 5, No. 3 (2023), presents a compelling examination of contemporary Muslim consumer behavior and financial practices in the digital age. The collection features four pioneering studies that explore the complex interplay between social psychology, digital literacy, and Islamic economic principles. Research spans from analyzing the social, psychological, and financial literacy dimensions of Muslim consumer behavior to investigating the determinants behind Muslim women's visits to viral social media destinations. The issue further addresses the crucial role of digital literacy in preventing Islamic banking fraud. This edition also reveals an in-depth assessment of the performance of tabarru' underwriting funds in Indonesia's sharia insurance sector. Collectively, these studies offer valuable insights for policymakers, financial institutions, and marketers seeking to understand and serve the modern Muslim market while maintaining alignment with Islamic ethical principles..